Deciding for Therapy: Deciding for Peace of Mind - Sattler, Janyne (Voluntas: Revista Internacional de Filosofia, 2022)
This paper tries to address the question of “philosophy as therapy” or of “therapeutic philosophy” from the point of view of Wittgenstein’s Tractatus Logico-Philosophicus against the picture of the “resolute” interpretation. The main points of interest are here the following ones: first, the reasons for undergoing therapy which, as I try to argue, have to be thought not only from a logical point of view, but also from an ethical one; and second, the decision involved in both the climbing up the Tractatus ladder and the want for cure and peace of mind – that is, the decision for therapy itself.